The Multivillage-Metropolis Baton Rouge. A Neopragmatic Landscape Approach. - Kühne, Olaf; Jenal, Corinna (Springer VS, 2020)
The capital of Louisiana, Baton Rouge, has been the scene of fundamental changes in recent decades. In the context of the tripole of petrochemistry, Louisiana State University (LSU) and public administration (especially of the state of Louisiana), which has been fully developed since the end of the 1920s, general processes (such as the transition from modern to post-modern spatial development) mix with specific local and regional characteristics and logics, also in dealing with spaces (such as the eccentric location of the downtown area, the limited influence of spatial planning). The result is a social-spatial formation of a 'multivillage metropolis'. The investigation of this 'multivillage metropolis' follows a neopragmatic approach that triangulates different theories, methods, data and researcher perspectives.
Keywords: Stadtentwicklung; Städtebauentwicklung; Moderne; Postmoderne; Stadtstruktur; Stadtlandschaft; Fußgängerverkehr; Stadtbildveränderung; Stadtimage; Alltagsleben; Stadtsoziologie; Stadtgeographie